First annual scientific conference - overview - Pyburn, Rhiannon (CGIAR Collaborative Platform on Gender Research, 2017)
Presented by Rhiannon Pyburn (KIT), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.